2001
DOI: 10.1128/mcb.21.9.3126-3136.2001
|View full text |Cite
|
Sign up to set email alerts
|

Vav-Rac1-Mediated Activation of the c-Jun N-Terminal Kinase/c-Jun/AP-1 Pathway Plays a Major Role in Stimulation of the Distal NFAT Site in the Interleukin-2 Gene Promoter

Abstract: The proto-oncogene product Vav, which is expressed specifically in hematopoietic and trophoblast cells, plays crucial roles in the development and activation of T cells triggered through the antigen-specific T-cell receptor (TCR) (7, 48). Vav enhances basal and TCR-activated transcription of the interleukin-2 (IL-2) gene, and this enhancement is largely mediated by activation of the distal NFAT element in the IL-2 gene promoter (NFAT-IL-2) (12, 24, 63). As in the case of other NFAT-binding sites (44), this ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
106
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(121 citation statements)
references
References 63 publications
(118 reference statements)
14
106
1
Order By: Relevance
“…We hypothesized that NFAT activation by Cybr was mediated by AP-1 rather than increased binding of NFAT proteins. Therefore, we utilized an NFAT reporter construct containing the distal IFN-␥ high affinity NFAT site, which does not include AP-1 binding sites (25). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We hypothesized that NFAT activation by Cybr was mediated by AP-1 rather than increased binding of NFAT proteins. Therefore, we utilized an NFAT reporter construct containing the distal IFN-␥ high affinity NFAT site, which does not include AP-1 binding sites (25). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Vav mediates NFAT activation but does not influence TCR-induced proximal PTK activation or the cytoplasmic calcium levels (29). Instead, Vav is more important for augmenting the TCR-induced JNK/AP-1 cascade upstream of NFAT activation (25). We have shown that Cybr expression enhances TCR-dependent phosphorylation of Vav, therefore linking these molecules Jurkat T cells were transfected with either X-press-EV or X-press-Cybr plasmids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression plasmids encoding Lck wild-type (wt) or mutant (F505) have been described previously (Choi et al, 1999). The pEFneo plasmid encoding human Vav-myc was kindly provided by Dr. Yun-Cai Liu (Kaminuma et al, 2001). The E. coli expression construct for the GST-Rho binding domain (RBD) of PAK1 was kindly provided by J.H.…”
Section: Plasmidsmentioning
confidence: 99%